Determinants of Quality of Life in Patients with Chronic Kidney Disease Undergoing Hemodialysis at Dr. M. Djamil Hospital Padang - Adilla, Friska; Nursal, Dien Gusta Anggraini; Triana, Vivi (Jurnal Kesmas Jambi, 2025)
Patients with Chronic Kidney Disease (CKD) encounter persistent health burdens that substantially affect their quality of life, particularly during treatment and hemodialysis. Consequently, identifying factors that influence quality of life in this population is essential. This study examined determinants of quality of life among CKD patients undergoing hemodialysis at Dr. M. Djamil General Hospital Padang in 2025. This study employed a mixed-methods approach with a concurrent triangulation design. The quantitative component used a cross-sectional design involving 73 patients selected through simple random sampling. Research instruments included the Kidney Disease Quality of Life–Short Form 36 and the Perceived Kidney Disease Self-Management Scale. Data were analyzed using univariate, bivariate, and multivariate analyses with logistic regression. The qualitative component applied a phenomenological approach through in-depth interviews with 15 informants, and the data were analyzed using thematic analysis. Overall, 53.4% of patients with chronic kidney disease undergoing hemodialysis reported low quality of life. Bivariate analysis showed that gender and disease perception were associated with quality of life, however, multivariate analysis identified only disease management perception as the dominant predictor. Patients with negative perceptions had a 33-fold higher risk of low quality of life compared to those with positive perceptions (p<0.001; OR=33.026; 95% CI: 6.124–178.106). No significant associations were found for age, education level, employment status, marital status, comorbidities, or duration of hemodialysis. Qualitative findings supported the quantitative results, showing that patients perceptions were influenced by informational, emotional, financial, and family support, which in turn improved disease acceptance, adaptation, and quality of life.